Maintaining and restoring balance in international payments - Fellner, William John; Machlup, Fritz; Triffin, Robert; Organisation for Economic Co-operation and Development (Princeton, N.J., Princeton University Press, 1966)
The primary purpose of the book was to help officials of the governments in their inquiry into the balance-of-payments problems, so essential in their negotiations of the necessary improvements of the international monetary system.
Revised versions of 17 papers prepared for a symposium held at the invitation of the Organization for Economic Cooperation and Development.
Includes index.
usc 30/04/18
Loans
Keywords: Balance of payments